2021
DOI: 10.1111/mec.16071
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics reveals variable patterns of immune gene evolution in monarch butterflies (Danaus plexippus)

Abstract: Humoral and cellular immune responses provide animals with major defences against harmful pathogens. While it is often assumed that immune genes undergo rapid diversifying selection, this assumption has not been tested in many species. Moreover, it is likely that different classes of immune genes experience different levels of evolutionary constraint, resulting in varying selection patterns. We examined the evolutionary patterns for a set of 91 canonical immune genes of North American monarch butterflies (Dana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…For example, positive selection produces genomic regions of reduced diversity through “selective sweeps,” whereby selected beneficial alleles, as well as neighboring sites, can increase in frequency within a population to the point of fixation ( Nielsen et al 2005 ). Recent studies on insects have applied population genetic approaches to investigate the genetic variability of immune genes, as well as to determine the different forms of selection acting upon them ( Palmer et al 2018 ; Tan et al 2021 ). However, with a few exceptions, studies employing genome-wide population genomic techniques to better understand how selection has acted on different functional classes of the immune system are still lacking, especially for nonmodel organisms within the field of genetics (but see Tan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, positive selection produces genomic regions of reduced diversity through “selective sweeps,” whereby selected beneficial alleles, as well as neighboring sites, can increase in frequency within a population to the point of fixation ( Nielsen et al 2005 ). Recent studies on insects have applied population genetic approaches to investigate the genetic variability of immune genes, as well as to determine the different forms of selection acting upon them ( Palmer et al 2018 ; Tan et al 2021 ). However, with a few exceptions, studies employing genome-wide population genomic techniques to better understand how selection has acted on different functional classes of the immune system are still lacking, especially for nonmodel organisms within the field of genetics (but see Tan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on insects have applied population genetic approaches to investigate the genetic variability of immune genes, as well as to determine the different forms of selection acting upon them ( Palmer et al 2018 ; Tan et al 2021 ). However, with a few exceptions, studies employing genome-wide population genomic techniques to better understand how selection has acted on different functional classes of the immune system are still lacking, especially for nonmodel organisms within the field of genetics (but see Tan et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evolutionary biology studies revealed that genes associated with the canonical immune system often evolve most rapidly, both within and between species ( 1 , 2 ). With the growing number of insect genomes and transcriptomes being sequenced, it has become evident that duplication and loss of immune genes are likely caused by host-pathogen interactions ( 1 , 2 ). Moreover, certain species react to various pathogenic challenges with a diverse array of specific responses (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic pleiotropy arises when a single gene product contributes to multiple discrete phenotypic traits, and many components of immune pathways appear to be pleiotropic. Since the discovery of the Toll pathway, for example, numerous studies (and indeed Nobel prizes) have recognized its conserved dual role in development and innate immune system signaling ( Lemaitre et al 1997 ; DiAngelo et al 2009 ; Anthoney et al 2018 ) and proposed that this could impose constraints on immune system evolution ( Obbard et al 2009 ; Tan et al 2021 ). More broadly, a recent study estimated that approximately 17% of human genes affect multiple discrete phenotypic traits, and functional enrichment analysis of this pleiotropic gene set revealed immune system functions to be among the most over-represented processes ( Sivakumaran et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%